Respuesta :

Answer:

Step-by-step explanation:

( a ). If input is 2  

2 × [tex]\frac{3}{4}[/tex] ÷ [tex]\frac{2}{3}[/tex] = [tex]\frac{3}{2}[/tex] × [tex]\frac{3}{2}[/tex] = [tex]\frac{9}{4}[/tex] = 2.25

If input is 2, then output is [tex]2\frac{1}{4}[/tex]

( b ). If output is 1/2

x × [tex]\frac{3}{4}[/tex] ÷ [tex]\frac{2}{3}[/tex] = [tex]\frac{1}{2}[/tex]

[tex]\frac{9}{8}[/tex] x = [tex]\frac{1}{2}[/tex]

x = [tex]\frac{1}{2}[/tex] ÷ [tex]\frac{9}{8}[/tex] = [tex]\frac{4}{9}[/tex]

If output is [tex]\frac{1}{2}[/tex] , then input is [tex]\frac{4}{9}[/tex]

Answer:

Step-by-step explanation:

a) input is 2

2 * 3/4 = 6/4

(6/4) / (2/3) = 18/8 or 2.25

b) output is 1/2 (this time we go backwards)

if it is multiply we divide and if it is divide we multiply

1/2 * (2/3) = 2/6        (it said divide by 2/3 so we multiply)

(2/6) / (3/4) = 8/18 or 4/9        (it said multiply by 3/4 so we divide)